2019
DOI: 10.1371/journal.pone.0218835
|View full text |Cite
|
Sign up to set email alerts
|

Mass evacuation and increases in long-term care benefits: Lessons from the Fukushima nuclear disaster

Abstract: BackgroundThough mass evacuation may increase the need for long-term care (LTC) services, how the need for LTC services increases and how the public LTC system affects it is not well understood. We evaluated changes in public LTC benefits for the people living in the mandatory evacuation areas established after the 2011 Fukushima nuclear disaster and examined the roles of the universal LTC insurance system in Japan.MethodsIn order to evaluate the effect of the mandatory evacuation on LTC benefits, we examined … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Regarding long‐term care insurance premiums, an increase in the number of older people requiring long‐term care and a decrease in the number of residents who pay the premium was found to affect its increase. Morita et al 15 showed that the cost of care in the disaster area increased with the use of light care, and Hasegawa et al 6 also showed a similar increase, especially in the evacuation area after the earthquake. Kobashi et al 16 revealed that older adults comprise the majority of the returning population, particularly between the age of 65 and 75 years.…”
Section: Discussionmentioning
confidence: 94%
“…Regarding long‐term care insurance premiums, an increase in the number of older people requiring long‐term care and a decrease in the number of residents who pay the premium was found to affect its increase. Morita et al 15 showed that the cost of care in the disaster area increased with the use of light care, and Hasegawa et al 6 also showed a similar increase, especially in the evacuation area after the earthquake. Kobashi et al 16 revealed that older adults comprise the majority of the returning population, particularly between the age of 65 and 75 years.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that the LTC costs for residents over 65 years in the former evacuation areas in Fukushima prefecture were approximately 1.5 times higher in 2012-2014 than before the earthquake. 3,6 This was caused by a marked increase in the utilization ratio of mild-degree LTC presumably due to the loss of informal at-home care. Currently, there is not enough information on whether the loss of informal care is more prominent in the evacuee or returnee groups hence, more information on family members is needed to properly understand the health care needs of those living in former evacuation areas.…”
Section: Discussionmentioning
confidence: 99%
“…When the elderly request to use the national public LTC service, municipal governments conduct interviews and surveys for living situation concerns. 3 The level of required LTC is determined by the Care Needs Certification Board, which is comprised of medical professionals and other specialists. 3…”
Section: Study Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the increase of disaster-related LTCI costs is an urgent issue in an aging society, few studies have examined the effect of disasters on LTCI costs. Community-based ecological studies showed changes in LTCI service after the GEJE [ 28 30 ]. However, there are no studies that examine the ever-changing effect of a disaster at the individual level chronologically and precisely.…”
Section: Introductionmentioning
confidence: 99%